In Vitro Antimycobacterial Activity of Human Lactoferrin-Derived Peptide, D-hLF 1-11, against Susceptible and Drug-Resistant Mycobacterium tuberculosis and Its Synergistic Effect with Rifampicin - Sorasak Intorasoot; Amornrat Intorasoot; Arocha Tawteamwong; Bordin Butr-Indr; Ponrut Phunpae; Chayada Sitthidet Tharinjaroen; Usanee Wattananandkul; Sirikwan Sangboonruang; Jiaranai Khantipongse (MDPI AG, 2022)
Tuberculosis is a highly contagious disease caused by the Mycobacterium tuberculosis complex (MTBC). Although TB is treatable, multidrug-resistant, extensively drug-resistant, and totally drug-resistant forms of M. tuberculosis have become a new life-threatening concern. New anti-TB drugs that are capable of curing these drug-resistant strains are urgently needed. The purpose of this study is to determine the antimycobacterial activity of D-enantiomer human lactoferricin 1-11 (D-hLF 1-11) against mycobacteria in vitro using a 3-(4,5-dimethylthiazol-2-yl)-2,5-dephenyltetrazolium bromide colorimetric assay, resazurin microplate assay, and microscopic observation drug susceptibility assay. Three previously described antimicrobial peptides, protegrin-1, AK 15-6, and melittin, with potent anti-TB activity, were included in this study. The findings suggest that D-hLF 1-11 can inhibit the growth of M. tuberculosis with a minimum inhibitory concentration of 100-200 µg/mL in susceptible, isoniazid (INH)-monoresistant, rifampicin (RF)-monoresistant, and MDR strains. The peptide can also inhibit some nontuberculous mycobacteria and other MTBC in similar concentrations. The antibiofilm activity of D-hLF 1-11 against the biofilm-forming M. abscessus was determined by crystal violet staining, and no significant difference is observed between the treated and untreated biofilm control. The checkerboard assay was subsequently carried out with M. tuberculosis H37Rv and the results indicate that D-hLF 1-11 displays an additive effect when combined with INH and a synergistic effect when combined with RF, with fractional inhibitory concentration indices of 0.730 and 0.312, respectively. The red blood cell hemolytic assay was initially applied for the toxicity determination of D-hLF 1-11, and negligible hemolysis (<1%) was observed, despite a concentration of up to 4 mg/mL being evaluated. Overall, D-hLF 1-11 has potential as a novel antimycobacterial agent for the future treatment of drug-sensitive and drug-resistant M. tuberculosis infections.